(untitled) (Journal of the College of Basic Education, 2022)
Symbol and encoding have often been used in international television dramas, which prompted some practitioners in this field to consider encoding as an important detail in the structure of the artistic image of a television drama. This research presents an attempt to detect coding levels in TV dramas and apply these levels procedurally to an Iraqi drama series. While the theoretical framework of the research included two topics:The first topic: the structure of the artistic image - which dealt with the presentation of the structure and composition of the image and the relationship of the artistic image with symbol and coding.